RDT: A New Data Replication Algorithm for Hierarchical Data Grid - Dayyani, Sheida; Khayyambashi, Mohammad Reza (International Journal of Computer Sciences and Engineering, 2015)
Grid computing is a type of distributed computing system that provides access to various computational resources which are shared by different organizations, in order to create an integrated powerful virtual computer. Nowadays, grid is known as an essential technology which is used for different kinds of high performance applications and it is believed that it will be applied more and more in the future as technology progresses. Data replication is a common method used in distributed environments to improve ease of data access and to provide a high level of data availability, increased fault tolerance and data reliability; and that’s why this method is used for data management in data grid systems. Since the data files are very large and the Grid storages are limited, managing replicas in storage for the purpose of more effective utilization requires more attention. In this paper, a novel data replication strategy, called Replication with Dynamic Threshold (RDT) is proposed that uses a new threshold for characterizing the number of appropriate sites for replication. Appropriate sites have the higher number of access for that particular replica from other sites. It also minimizes access latency by selecting the best replica when various sites hold replicas. The simulated results with OptorSim, i.e. European Data Grid simulator show that the RDT strategy gives better performance compared to the other algorithms and prevents the unnecessary creation of replicas which leads to efficient storage usage.